Evaluation of the Potential for Territorial Ecological Restoration: A Case Study of Zhaoping County, China - Min Liu; Xinwei Liu; Heju Huai; Xiumei Tang (Land, 2023)
Territorial ecological restoration (TER) is a critical step for promoting the development of an ecological civilization, as well as a significant strategic task relating to national ecological security and the well-being of a population. However, calculating the ecological restoration potential (ERP) is a key challenge in TER. Using Zhaoping County as an example, this study calculated the ecological restoration natural potential (ERNP), including the vegetation coverage potential, water conservation potential, windbreak and sand fixation potential, and biodiversity potential, and proposed an ERP calculation method based on the correction of ERNP with an ecological security pattern (ESP) and social support (SS). The findings revealed several key points. First, using the similarity habitat method to calculate ERNP highlighted significant disparities in the vegetation coverage, water conservation, windbreak and sand fixation, and biodiversity across Zhaoping County. These variations were contrary to regional ecological service functions. Second, overall, the ESP levels in Zhaoping County were high, accounting for about 60.42% of its total area being classified as high or relatively high level, with the towns exhibiting strong SS abilities primarily located in the northern region. Third, the ERP results which are between 0 and 1 indicated that areas with higher potential were mainly found in the west and northeast of Zhaoping, while lower potential areas were concentrated in the northwest and south; of them, the ERP index value in most regions is between 0.2 and 0.3, accounting for about 43.97% of the area. Finally, suggestions for the TER project layout and measures to enhance the ERP were proposed based on these ERP calculations. This study offers new insights into ERP strategies while providing guidance for identifying critical areas requiring restoration.